λ-MnO2 Thin Films with Sponge-Like Structures: Synthesis, Characterization and Physiochemical Applications - Khalid Abdelazez Mohamed Ahmed (Universitas Gadjah Mada, 2021)
Manganese dioxide has acquired significant research attentiveness in many fields over the past years because of its exciting physicochemical features. The magnetized λ-MnO2 thin films with sponge-like structures (TSLs) were prepared by hydrothermal-soft chemical and delithiation-lithium manganese process. The XRD, XPS, EDX, FESEM, TEM, HR-TEM, and N2 adsorption-desorption techniques were used to characterize the as-prepared product’s structure composition, morphology, and surface area. The particle growth details of λ-MnO2 are postulated by the oxidation-ionic change-delithiation (OID) mechanism. The electrochemical property was analyzed by galvanostatic discharge-charging, electrochemical impedance spectrum (EIS), and cyclic voltammetry (CV). Special attention of λ-MnO2 S.L.s is given to their applications in the degradation of methyl orange (MO) from wastewater under O2 air bubble pump and cathodic substance in the lithium-ion battery. Due to the peculiarity crystal form and morphology face, the λ-MnO2 TSLs might be promisingly applied in the various physicochemical area.